TINGKAT KEPUASAN BERDASARKAN RESPON PENGHUNI RUMAH SUSUN SEWA KASNARIANSYAH PALEMBANG - Dafrimon Dafrimon (PILAR, 2014)
The solution provided by the government to meet the residence habitable for residents on low incomes are flat, so that in the long term the government can concentrate on a simple home-based apartment rental (Rusunawa). in serving the needs of the people there are limitations that are still encountered.The aim of this study is determine the level of occupant satisfaction, by comparing the quality of service expected from residents and the quality of care received. Results from the adaptation of hosts with a jug of behavior influence and impact on the level of satisfaction.Locations used for research on the Flats are managed by PD. Sarana Pembangunan Palembang Jaya (PD. SP2J) located in Kasnariansyah Street.This study shows that residents in the Flats PD. Sarana Pembangunan Palembang Jaya not satisfied with thequality of care they receive, because there are gaps and level of satisfaction based on dimensions of Tangibles 0.01 and 1.00, Realibility 0.00 and 1.00, Responsive 0.00 and 1.00, Assurance 0.02 and 1.01, Emphaty 0.02 and 1.01 In the analysis of a Cartesian diagram obtained Rusunawa Kasnariansyah statement that residents of the 35 attributes/statement only 21 attributes/statements are satisfied and 6 attributes/ statements which need to be processed.To meet the satisfaction level of residents, managers Flats Rusunawa Kasanriansyah need to do a repair of the interior design, playgrounds and expand the walkaways.